Biomarkers in Paediatric Cystic Fibrosis Lung Disease. (September 2015) - Ramsey, Kathryn A.; Schultz, André; Stick, Stephen M.
Summary: Biomarkers in cystic fibrosis are used i. for the measurement of cystic fibrosis transmembrane regulator function in order to diagnose cystic fibrosis, and ii. to assess aspects of lung disease severity (e.g. inflammation, infection). Effective biomarkers can aid disease monitoring and contribute to the development of new therapies. The tests of cystic fibrosis transmembrane regulator function each have unique strengths and weaknesses, and biomarkers of inflammation, infection and tissue destruction have the potential to enhance the management of cystic fibrosis through the early detection of disease processes. The development of biomarkers of cystic fibrosis lung disease, in particular airway inflammation and infection, is influenced by the challenges of obtaining relevant samples from infants and children for whom early detection and treatment of disease might have the greatest long term benefits.